Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
URI: https://scholar.sun.ac.za/handle/10019.1/128896
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Infringement of Brand Rights on Different Products Is an Illegal ACT - Fahdia, Khamada Wafi; Roisah, Kholis (International Journal of Social Science Research and Review, 2023)
The study aims to find out how the provisions of the law are in violation of brand rights to nongender products and their protective forms, as well as how legal efforts should be made in violation of their laws. Legal protection for legitimate brands' owners is regulated within brand laws intended to give their owners exclusive rights. Legal measures that rights holders can make on broken brands can be made either by civil law or criminal law. Indonesia's brand registration system is a constituent system, and it is recommended that all efforts be quick to register a trademark or service brand for the creditor of intellectual property rights. The holding of a brand would be wise to appeal to the court immediately if there is any indication that a brand offense is committed by another and the cost is not greater.
Keywords: Brands Infringement; Products of No Kind; Unlawful Conduct

Analysis of Intellectual Property Rights Disputes Between PS Glow and MS Glow in View of Law No. 20 of 2016 Concerning Marks and Geographical Indications (Analysis of Decision of Case Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby) - Gracia, Indiera Fortuna; Kurniawan, Kurniawan; Sili, Eduardus Bayo (International Journal of Social Science Research and Review, 2023)
This study analyzes intellectual property rights disputes between PSGlow and MSGlow in terms of Law no. 20 of 2016 concerning Trademarks and Geographical Indications (analysis of case decision number: 2/pdt.sus.HKI/Merek/2022/pn.niaga Sby) which aims to explain and analyze the basic considerations of Surabaya Commercial Court judges in accepting lawsuits, explaining and analyzing how is the legal protection of trademarks that have been registered based on Law No. 20 of 2016 concerning Trademarks and Geographical Indications, explaining and analyzing whether there is an element of passing off between PS Glow and MS Glow based on Case Decision Number: 2/Pdt.Sus.HKI /Merek/2022/PN. Niaga Sby.The legal materials in this research are primary, secondary, and tertiary legal materials using normative research methods.The basis for consideration is that a lawsuit was filed from PS Glow for the use of the brand without rights against MS Glow. and legal protection for brands that have been registered under Law no. 20 of 2016 concerning Marks and Geographical Indications, namely that the penalties that will be imposed on these counterfeiters can be in the form of imprisonment, imprisonment and fines, as referred to in articles 100 to 102 of Law No. 20 of 2016 concerning Marks and Geographical Indications. and between PS Glow and MS Glow there is no element of passing off based on Case Decision Number: 2/Pdt.Sus.HKI/Merek/2022/PN.Niaga Sby, because the MS Glow brand registers its brand in HAKI in class 32 with the classification of powdered drinks and PS Glow registered their brand on Intellectual Property Rights in class 3 with a cosmetic classification.
Keywords: Brand; IPR; Passing off

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
URI: http://hdl.handle.net/10019.1/127343
Keywords: Antitrust law; Australia; Competencia; Competition Act; 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

Legal Protection of Trade Secret from the View of Civil and Criminal Law - Atika, Atika (International Journal of Social Science Research and Review, 2023)
Indonesia has ratified the WTO/TRIPs Agreement convention and is in full compliance and non-reservation, the insistence of developed countries’ owners of Intellectual Property Rights against Indonesia, and the need for national Intellectual Property Rights. By looking at the above, legal protection is needed for every product and service, especially licenses for trade secrets in the Intellectual Property Rights component. The state imposes criminal sanctions on violators of Trade Secret rights as stipulated in chapter 17 (1) constitution number 30/2000. However, it is also hoped that the act of imposing sanctions by the state will return to the interests of the protected party by making the crime a complaint offense chapter 17 (2) constitution number 30/2000. There are repressive legal actions that can be carried out as chapter 11 constitution number 30/2000 states that the holder of trade secret rights or the licensee may sue anyone who deliberately or without rights commits the actions referred to in the article in the form of (a). Compensations claim and/or; (b). Cessation of all actions referred to in chapter 4 constitution number 30/2000.
Keywords: Intellectual Property Rights; Legal Protection; Trade Secrets

Intellectual Property Law in Africa: Harmonising Administration and Policy - Ncube, Caroline B. (Taylor & Francis, 2023)
Examining the harmonisation of Intellectual Property policy, law and administration in Africa, this book evaluates the effectiveness of efforts to establish continental Intellectual Property institutions and frameworks. It also considers sub-regional initiatives led by the regional economic communities and the regional Intellectual Property organisations, focusing on relevant protocols and agreements that address Intellectual Property as well as the implementing institutions. The book assesses the progress of such initiatives with particular reference to the current socio-economic status of African states. It argues that that harmonisation initiatives need to be crafted in a way that is supportive of the developmental goals of African states and advocates for due consideration of individual states’ unique conditions and aspirations. This book will be of great relevance to scholars and policy makers with an interest in Intellectual Property law and its harmonisation in Africa.
Accepted: 2023-06-22T09:36:20Z
Keywords: Africa; Droit (harmonisation); Intellectual property; Public interest; TRIPs; governance; thema EDItEUR::G Reference

Arbitrability of Intellectual Property Dispute: A Pragmatic Dispute Resolution Mechanism - Singh, Vaishali (International Journal of Science and Research, 2023)
Conventionally, conflicts over intellectual property rights have been addressed primarily in national courts. Nonetheless, there has been a considerable inclination towards arbitration in recent years. For example, the number of cases decided under the WIPO Arbitration and Mediation Rules is constantly increasing, and the number of specific IP-related arbitral institutions is rising as well. This is due, in part, to the territorially limited reach of state court procedures, which no longer match the needs of modern international commercial processes. The transition to arbitration is appropriate since arbitration is particularly well suited to settling intellectual property conflicts. Arbitration is a private process, which is especially beneficial in IP issues due to the sensitive nature of the material involved. Furthermore, specific knowledge is necessary to properly settle technological disputes, a challenge that might be overcome by choosing adequately competent arbitrators.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Intellectual property; WIPO (World Intellectual Property Rights Organization)

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels